Characterisation of kinematic hardening and yield surface evolution from uniaxial to biaxial tension with continuous strain path change - Merklein, Marion; Suttner, Sebastian; Brosius, Alexander (CIRP Annals - Manufacturing Technology, 2014)
With respect to multistage forming processes the material behaviour and the history of the strain path during the process is of special interest for the improvement of the numerical prediction of forming processes. While different researchers investigated the Bauschinger effect during a load reversal and biaxial loading with pre-strained specimens, in this paper the yield locus evolution in the first quadrant of the principles stress space under biaxial loading of a modified cruciform specimen without test interruption is presented. The movement of the yield surface centre caused by kinematic hardening is approximated by an alternative approach based on experimental results. © 2014 CIRP.
LFT Import::2019-07-29 (2026)
Keywords: Kinematic hardening; Sheet metal; Stress